INTERPRETAÇÃO E DIREITO NATURAL: ANÁLISE DO TRATADO DE DIREITO NATURAL DE TOMÁS ANTÔNIO GONZAGA (Revista de História Regional, 2007)
At the end of the 18th. century, becoming a lawyer in Coimbra, Tomás Antonio Gonzaga wrote the Tratado de Direito Natural, with the intention to write the first book in Portuguese about the recent dispositions of natural law, joing the theological christian principles of the society's orientation. Basing in the original formulations about the concept of natural law, the purpose of this article is to discuss the concepts of Gonzaga, comparing with Grotius and Pufendorf, considered the founders of the "modern school of natural law", with Heineccius, who interpreted the ideas of these philosophers with a theological obliquity as Antonio Ribeiro dos Santos, his contemporaneous in Portugal. At the end, some considerations had been made about the conceptions of natural law observed on and after the government of Pombal, relating the interpretation possibilities from the magistrates, of the legislation in activity.